Concevoir la synergie des cycles pour promouvoir un métabolisme agri-urbain écologiquement efficient et réduire l’exposition humaine aux polluants - Camille Dumat; Antoine Pierart (VertigO)
At the global scale, cities concentrate the majority of humanity and in the same way as facilities classified for the protection of the environment (ICPE regulation, France) they aim to increase the sustainability of practices in order to reconcile human activities, environmental issues, human health and well-being of the populations. In this context, sustainably designing the reduction of material flows and circular economy in (peri)urban areas, thanks to a deliberately interdisciplinary and de-compartmentalized approach, is a crucial objective in terms of reducing environmental-health risks and ecological inequalities. The sustainable management of persistent metallic pollutants in urban agriculture projects thus appears as an opportunity to promote the ecological transition : scientific popularization, citizen consultations, otherness and sustainable food are directly involved. Research results concerning four metal elements commonly observed in urban ecosystems : lead, cadmium, copper and antimony, are discussed in the context of urban agriculture projects to illustrate these essential reflections to design the synergy of biogeochemical and living products cycles and promote an ecologically efficient urban metabolism to reduce human exposure to pollutants.